Odpowiedzi

2009-11-22T15:43:58+01:00
A)-3(2x+7)=-5x+7
b)-4(a-b)=-4a+4b
c)7(5-c)=35-7c
d)-12(-jedna trzecia +z)=
e)a(a-b)=akwadrat-ab
f)2a(3a-2)=6akwadrat-4a
g)-x(5y+x)=-5xy+xkwadrat
h)-2x(-2x-3+y)=-2xkwadrat-6x+2xy
i)(2x+6):2=
j)(3x-12):3=
k)(4x-8):(-2)=
l)(10x+15):5=
2009-11-22T15:45:53+01:00
A) -6x - 21
b) -4a + 4b
c) 35 - 7c
d) 4 - 12z
e) a do kwadratu - ab
f) 6 a do kwadratu - 4a
g) -5xy - x do kwadratu
h) 4 x do kwadratu + 6x - 2xy
i) x + 3
j) x-4
k) -2x + 4
l) 2x + 3
Najlepsza Odpowiedź!
2009-11-22T15:46:42+01:00
A)-3(2x+7)=-6x-21
b)-4(a-b)=-4a+4b
c)7(5-c)=35-7c
d)-12(-jedna trzecia +z)=21/3-12z=7-12z
e)a(a-b)=a do kwadratu -ab
f)2a(3a-2)=6a do kwadratu-4a
g)-x(5y+x)=-5xy-x do kwadratu
h)-2x(-2x-3+y)=4x do kwadratu+6x-2xy
i)(2x+6):2=x+3
j)(3x-12):3=x-4
k)(4x-8):(-2)=-2x-4
l)(10x+15):5=2x+3